Exploring varietal uptake through a gender lens: Insights from a multi-country, multi-crop qualitative study - Cavicchioli, Martina (International Institute of Tropical Agriculture, 2023)
This contribution presents the preliminary results of a qualitative study complementing an experimental design conducted in Nigeria, Kenya, Ethiopia, Uganda, and India under Work Package 3 of the One CGIAR Market Intelligence initiative. The aim of this multicrop and multicountry study is to understand the factors driving or hindering women and men producers and consumers in varietal adoption. By showcasing evidence collected through focus group discussions and interviews with farmers from various gendered social groups and seed-sector actors, this qualitative study aims to contribute a gender perspective to behavioral intelligence research that will ultimately inform both global and country-specific equitable seed promotion and delivery strategies and accelerate the uptake of gender-responsive varieties. Our results suggest behavioral attitudes such as risk aversion based on previous experiences with improved variety and knowledge gained through community seed- delivery channels or peer-to-peer exchanges are critical in driving decisions about varietal adoption for both women and men. However, if unpacked through a gendered, intersectional lens, behavioral attitudes appear as a composition of multiple barriers and drivers that are differently experienced and, most importantly, prioritized by women and men. Among the most reoccurring are trait preferences (as referred to local production and consumption habits as well as gender roles in crops’ farming and processing), access to seed promotion and dissemination channels (radio, extension services, champion farmers), participation in community networks, availability of fertile soil, and income.